2005
DOI: 10.1093/jnci/dji073
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Possible Reactivation of Human Papillomavirus in Human Immunodeficiency Virus–Positive Women

Abstract: In HIV-positive women, plasma HIV RNA level and CD4+ count in combination appear to have a strong and statistically interactive association with incident detection of HPV, some of which may reflect HPV reactivation (e.g., in sexually inactive women). The more moderate association between HIV coinfection and HPV persistence could partly explain why cervical cancer rates have not reached more epidemic proportions in HIV-positive women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
454
4
26

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 461 publications
(510 citation statements)
references
References 48 publications
26
454
4
26
Order By: Relevance
“…We also found that HIV-1 infection was independently associated with an increase in SIL among HPV-positive women and that HIV-1 represented an important risk factor for the presence of HSIL. These findings are in agreement with other African series (La Ruche et al, 1998;Chirenje et al, 2002;Hawes et al, 2003) and with many studies in industrialised countries (Sun et al, 1997;Ahdieh et al, 2001;Moscicki et al, 2004b;Strickler et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that HIV-1 infection was independently associated with an increase in SIL among HPV-positive women and that HIV-1 represented an important risk factor for the presence of HSIL. These findings are in agreement with other African series (La Ruche et al, 1998;Chirenje et al, 2002;Hawes et al, 2003) and with many studies in industrialised countries (Sun et al, 1997;Ahdieh et al, 2001;Moscicki et al, 2004b;Strickler et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the high background prevalence of human immunodeficiency virus type 1 (HIV-1) observed in many African settings adds complexity to our understanding of the epidemiology of HPV and cervical neoplasia. Studies conducted in industrialised countries have shown that HIV-1 alters the natural history of HPV infection by upregulating HPV persistence and recurrences, thereby facilitating progression to high-grade lesions and cancer (Sun et al, 1997;Ahdieh et al, 2001;Strickler et al, 2005). Consequently, cervical cancer has been included in the list of AIDS-defining opportunistic conditions by the Centres for Disesase Control and Prevention (Centers for Disease Control and Prevention, 1993).…”
mentioning
confidence: 99%
“…Among women, RTIs often go undiagnosed and untreated. It is a burden of asymptomatic disease, which is responsible for the frequent and severe long-term morbidity and in part for the persistence and spread of sexually transmitted diseases (STIs) in the community [2].…”
Section: Discussionmentioning
confidence: 99%
“…Keywords HIV Á Squamous cell abnormalities Á Intraepithelial lesions Á Pap smear Introduction HIV-infected women have a higher risk of human papilloma virus (HPV)-associated cervical intraepithelial neoplasia as compared to HIV-uninfected women [1][2][3][4][5]. The overwhelming majority of women affected by this completely preventable disease reside in resource-constrained nations where access to screening services is limited or non-existent.…”
mentioning
confidence: 99%
“…Die Ursache für eine Viruspersistenz ist unklar, hängt aber vermutlich ebenfalls mit einem Versagen der T-Zell-vermittelten Immunität ab, wie die deutlich höheren Raten persistierender und progredienter HR-HPV-Infektionen bei immunsupprimierten oder HIV-positiven HR-HPV-infizierten Menschen zeigen [29].…”
Section: Hpv-persistenzunclassified